2009
DOI: 10.1002/elan.200900232
|View full text |Cite
|
Sign up to set email alerts
|

SECM Imaging of Interfacial Processes in Defective Organic Coatings Applied on Metallic Substrates Using Oxygen as Redox Mediator

Abstract: Operation of the SECM in feedback mode over a coated metal allows changes in the state of the surface to be monitored using dissolved oxygen in the test environment as redox mediator. The system investigated consisted in mild steel samples coated with a polyurethane film in which a defect was deliberately introduced into it. Accurate approach curves under negative-feedback condition were obtained using a platinum microelectrode over regions of the intact coating. Imaging experiments were also carried out over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…The SECM is an effective ''in situ'' method for the investigation of coated or uncoated metals [51][52][53][54][55][56]. Here, SECM feedback mode is employed to monitor the swelling of epoxy coating by measuring the tip-substrate distance which is derived from the decreased feedback current with the assistance of approach curve [57,58].…”
Section: Secmmentioning
confidence: 99%
“…The SECM is an effective ''in situ'' method for the investigation of coated or uncoated metals [51][52][53][54][55][56]. Here, SECM feedback mode is employed to monitor the swelling of epoxy coating by measuring the tip-substrate distance which is derived from the decreased feedback current with the assistance of approach curve [57,58].…”
Section: Secmmentioning
confidence: 99%
“…Deliberate addition of mediators is controversial in corrosion studies as they may influence the corrosion behavior [30]. Therefore, several SECM corrosion studies [20,[31][32][33][34][35] have exploited molecular oxygen O 2 naturally present in the solution. In the present paper we demonstrate how TSV-SECM using O 2 detection at nanostructured Pt MEs is applied to investigate and to identify redox processes from the complex voltammetric response of the electrocatalysts.…”
Section: A1mentioning
confidence: 99%
“…Thus, this technique has proven to be a very useful tool for studying a wide range of corrosion processes, including bimetallic corrosion, [1][2][3] dissolution of inclusions in alloys, [4][5][6] controlled generation of single pits in otherwise passive metals, [7][8][9] monitoring of precursor sites for pit nucleation in oxide layers [10][11][12] as well as detection of the metastable pitting regime [13,14] and the onset of corrosion processes from defective coatings. [15][16][17][18] Two recent reviews on further uses of SECM in the field of corrosion can be found in references [19,20].…”
Section: Introductionmentioning
confidence: 99%